2021
DOI: 10.1002/slct.202100886
|View full text |Cite
|
Sign up to set email alerts
|

Claisen‐Schmidt Condensation and Domino Claisen‐Schmidt Condensation ‐ Michael Addition of 16‐Formyl Steroids in the Presence of Switchable Polarity Solvents

Abstract: Switchable polarity solvents (reversible ionic liquids) have been used to replace conventional catalysts and solvents in Claisen-Schmidt condensation reactions of 16-formyl steroids and aromatic ketones. The primarily formed α,β-unsaturated ketones may undergo a Michael addition with the aromatic ketone reaction partner. By the proper choice of the reaction conditions, either the α,β-unsaturated ketone or the products of the domino Claisen-Schmidt condensation -Michael addition could be obtained with good sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Previously, it was demonstrated that the two-component system containing tBu-TMG (5) and ethylene glycol is not reusable due to the difficulties in the removal of carbon dioxide from the mixture in the ionic state. [31] According to the present experiments, the MTBD (6)/ethylene glycol mixture showed equally excellent activity (Table 1, entries 22,23). If this mixture, in contrast to tBu-TMG/ ethylene glycol offers the advantage of re-usability by absorption and removal of carbon dioxide, it can be an excellent catalyst/solvent for synthesis of steroid derivatives in the Claisen-Schmidt condensation.…”
Section: Recyclability Of the Mtbd (6)/ethylene Glycol Mixturementioning
confidence: 63%
See 3 more Smart Citations
“…Previously, it was demonstrated that the two-component system containing tBu-TMG (5) and ethylene glycol is not reusable due to the difficulties in the removal of carbon dioxide from the mixture in the ionic state. [31] According to the present experiments, the MTBD (6)/ethylene glycol mixture showed equally excellent activity (Table 1, entries 22,23). If this mixture, in contrast to tBu-TMG/ ethylene glycol offers the advantage of re-usability by absorption and removal of carbon dioxide, it can be an excellent catalyst/solvent for synthesis of steroid derivatives in the Claisen-Schmidt condensation.…”
Section: Recyclability Of the Mtbd (6)/ethylene Glycol Mixturementioning
confidence: 63%
“…catalysts in the Claisen-Schmidt condensation of 17-oxo- [30] and 16-formyl steroids [31] in the presence of methanol [30] or ethylene glycol. [30,31] As the nBu-TMG/ethylene glycol mixture had been found to form a readily reversible system, [30,31] and made it possible to recycle both the base and the alcohol, the reaction of 17α-methyl-18-nor-13α-16-oxo steroid (1) and benzaldehyde (2 a) was first carried out in the presence of a mixture of these components (Table 1, entry 1). Unfortunately, only low conversion was achieved under conditions identical to those applied in the synthesis of 16-arylidine derivatives before.…”
Section: Claisen-schmidt Condensation Of 17α-methyl-18-nor-13α-16-oxo...mentioning
confidence: 99%
See 2 more Smart Citations
“…Steroid-ferrocene derivatives 111 and 112 were obtained via the Claisen-Schmidt condensation of the corresponding 16-formyl steroids and acetylferrocene (110), carried out in a nBu-TMG (2-n-butyl-1,1,3,3tetramethylguanidine) and ethylene glycol mixture (Scheme 20). 54 nBu-TMG can play a dual role of co-solvent and catalyst to substitute the usual alkali hydroxides. In similar reactions, both nBu-TMG and ethylene glycol can be recycled via the formation of a reversible ionic liquid in the presence of CO2.…”
Section: Transformation Of Steroids With Carbonyl Functionalitymentioning
confidence: 99%